Pertumbuhan dan Produktivitas Rumput Odot yang diberi Feses Sapi yang Difermentasi - Eryc Ramanda Putra; Media Agus Kurniawan (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study is to ascertain the development and productivity of Odot grass in the presence of fermented cow dung. This study used a completely randomized design (CRD) non-factorial research method consisting of 4 treatments and 5 replications. An experiment was conducted using the parameters of odot grass plant height, number of odot grass leaves, fresh forage production, and dry forage production to ascertain the impact of feeding fermented cow feces on the growth of odot grass (Pennisetrum purpureum Cv.Mott) in order to yield the best results. When odot plants are treated according to the level of need, the best treatment is the provision of fermented cow feces fertilizer. This has a significant impact on the growth and productivity of odot grass, allowing it to produce maximum results in terms of plant height, number of leaves, fresh forage, and dry weight. 200 grams, one odot grass cutting, 100 milliliters of water, and a polybag with a 1:10:50 fermentation ratio.